DNA Protection by an Aronia Juice-Based Food Supplement - Tamara Bakuradze; Peter Meiser; Jens Galan; Elke Richling (MDPI AG, 2021)
Background: This study investigated the effects of an aronia juice-based food supplement on background and total DNA strand breaks in whole blood, and on H2O2-induced DNA strand breaks in isolated peripheral blood lymphocytes. Methods: Ninety-one healthy volunteers were randomly selected to consume either the food supplement (2 × 25 mL drinking ampules, n = 45) or no supplement (n = 46) daily for eight weeks. Results: Background DNA strand breaks decreased significantly after four and eight weeks of supplement consumption, compared to baseline (p < 0.05), but the overall effect was low, and neither group showed a decrease in total DNA strand breaks. Conversely, supplement consumption clearly reduced H2O2-induced DNA strand breaks ex vivo (p < 0.001), with statistically significant reductions after four and eight weeks, compared to the control group (p < 0.05). Conclusions: Thus, although consuming antioxidant supplements might produce only marginal immediate benefits under healthy conditions, potential preventive effects warrant further investigation.